Interfering antibodies may contribute to elevated d-dimer: a case report - Dorte B. Zilstorff; Thomas Steffen Hermann; Christine Rasmussen; Dorte Husum; Jørn Dalsgaard Nielsen; Nicolai J. Wewer Albrechtsen (Journal of Medical Case Reports, 2024)
Abstract Background Plasma levels of d-dimer are elevated in patients with thromboembolisms. Here we investigated the existence of interfering antibodies as a potential cause for elevated d-dimer levels. Case presentation A 42-year-old white Caucasian woman with a prior history of pulmonary embolism during her first pregnancy (treated with heparin therapy for 6 weeks postnatally) and hypothyroidism had a persistent elevated d-dimer without any clinical or ultrasound-based signs of thromboembolic conditions during her second pregnancy. We obtained informed consent and plasma was obtained from the patient. d-dimer levels were measured using two different assays. We also tested for the presence of rheumatoid factor, performed dilution series, and finally used an antibody depletion strategy. The two d-dimer assays performed similarly. Using our antibody depletion technique, we observed that ~ 1/3 of the increased plasma levels of d-dimer may be attributed to interfering antibodies. Conclusions Our results identify interfering antibodies as a potential contributor to an increased d-dimer in this patient. Our case highlights the potential of heterophilic interference for increased d-dimer and provides a procedure to determine this analytically.